Benin : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2004)
This report reviews developments in Benin during 2003 in the context of the Sixth and Final Review Under the Poverty Reduction and Growth Facility (PRGF) arrangement. The report sets forth the policies and measures the government intends to implement during 2004 in the context of its poverty reduction strategy. It assesses the country's economic and financial progress since 2000, when the current arrangement was approved by the IMF. The report highlights that Benin's macroeconomic performance was broadly in line with the program objectives in 2003.